Theses on Institutional Planning and Research at Universities - Badat, Saleem (South African Journal of Higher Education, 2016)
The theme of this Forum is Enhancement and your Forum announcement correctly recognises that a “culture of continuous enhancement of quality and reflective practices is critical to the well-being of a university”, and that as institutions we need “to operate more efficiently and effectively in a resource constrained environment”. I wish to advance a number of theses in order to frame as well as engage with the activities of institutional research and planning as part of the “critical self-reflection” that the Southern African Association for Institutional Research seeks to promote.